Extending the Technology Acceptance Model for Augmented Reality Learning: The Influence of Computational Thinking and Abstract Thinking Skills - Fakhrur Rozi; Pujiriyanto Pujiriyanto (Journal of Educational Sciences, 2026)
Augmented Reality (AR) can visualize abstract electronics concepts, but its educational value depends on students’ acceptance and use. This study aimed to explain vocational students’ actual system use of AR by extending the Technology Acceptance Model (TAM) with computational thinking and abstract thinking. A quantitative cross-sectional survey involved 151 Audio-Video Engineering and Industrial Electronics Engineering students at SMK Negeri 1 Padang. The school was purposively chosen because AR had not been integrated into its Electronics Engineering classes, while the curriculum includes abstract concepts suited to three-dimensional visualization. Respondents were selected through purposive sampling after a standardized AR BASIC ELECTRONICS session. The sample exceeded the minimum PLS-SEM requirement and was appropriate because participants had direct AR experience and relevant technical backgrounds. Data from a 29-item five-point Likert questionnaire were analyzed using PLS-SEM in SmartPLS3. The measurement model met validity and reliability criteria. Computational and abstract thinking significantly influenced perceived usefulness and actual system use, but not perceived ease of use. Perceived usefulness significantly influenced actual system use, whereas perceived ease of use did not. The model explained 59.6% of the variance in actual system use, indicating that cognitive readiness and perceived usefulness are central to AR acceptance in vocational education.